Mesozoic crustal thickness variations and related hydrothermal Cu mineralization in eastern Heilongjiang and Jilin Provinces, China. Issue 11 (24th July 2021) - Liu, Yang; Sun, Jinggui; Zhang, Yong; Han, Jilong; Chu, Xiaolei
ABSTRACT: Ocean-continent subduction drives sequential geologic events, including upwelling of mantle magmas and delamination of thickened lithosphere, which lead to crustal thickness variations and metallic enrichment or depletion at crustal roots. This paper estimates the crustal thickness in eastern Heilongjiang and Jilin Provinces based on La/Yb ratios of crust-derived I-type granites formed by Mesozoic Palaeo-Pacific slab westward subduction beneath Eurasia and assesses the related hydrothermal Cu mineralization. During the flat subduction phase (210–160 Ma), the continental crust dramatically thickened from 32 ± 6 km to 58 ± 6 km, indicating that much mafic magma accumulated under the ancient crust; notably, 210–177 Ma granitoids were generated in the thinner crust because of their normal arc natures, and subsequent remelting of mafic cumulates in the thicker crust formed adakitic magmas (~177–165 Ma) with low MgO (0.03–1.38 wt.%). From 140 to 95 Ma, the steep subduction of the dense slab drove regional decompression and consequent delamination and thinning of the lithosphere from ~58 km to 23 km, inducing explosive volcanic activity along with limited hydrothermal Cu deposition. Most Cu mineralization was associated with normal arc magmas; therefore, we speculate that two key factors were responsible for the small volume of Cu deposition: (1) thinner crust under an extensional setting failed to suppress voluminous pyroclastic eruptions, causing the dissipation of volatiles and preventing a large magma reservoir with long-lasting shallow differentiation; (2) root removal of thickened crust led large volumes of sulphide cumulates, if present, to founder into the mantle rather than remain in the crust, which greatly depleted Cu in the ascending melts. Graphical Abstract: uf0001